Co‐Developing User‐Centred Nutrition Educational Resources to Integrate Nutrition Into Multiple Sclerosis Care: A Collaborative Approach With Healthcare Professionals and Healthcare Consumers. - Allogmanny, Shoroog; Probst, Yasmine; Zoszak, Karen; Stefoska‐Needham, Anita (Health Expectations, 2026)
Introduction: Nutrition is often overlooked in multiple sclerosis (MS) care, leading to a gap in comprehensive patient management. Developing MS‐specific nutrition educational resources could address this gap. This study therefore aimed to collaboratively develop MS‐specific nutrition educational resources with healthcare professionals (HCPs) and people living with MS (plwMS) to support the future integration of nutrition into MS care. Methods: A three‐phased qualitative study was conducted, guided by the Design Thinking framework. Phase 1 involved separate online workshops with HCPs and plwMS, alongside semi‐structured interviews with HCPs, to explore needs and challenges related to nutrition in MS care, and to generate solution‐focused ideas for resource development. Phase 2 focused on developing prototypes. Phase 3 included usability testing of the co‐developed prototypes through online and face‐to‐face interviews with HCPs and plwMS. Data from Phases 1 and 3 were analysed using an inductive, reflexive thematic analysis. Results: Two workshops (n = 9 HCPs; n = 14 plwMS) and ten HCP interviews were conducted in Phase 1, generating four themes: (1) Addressing healthcare barriers to providing nutrition education in MS care; (2) Supporting person‐centred nutrition communication; (3) Fostering equity through accessible and inclusive MS‐specific educational resources; and (4) The integral role of the dietitian in MS care. A set of new nutrition‐resource prototypes, informed by Phase 1 theme‐based design considerations, was co‐developed and hosted on a website (Phase 2). In Phase 3, 18 HCPs and 15 plwMS provided feedback on the prototypes, grouped across four themes: (1) Clear, targeted messaging; (2) Visually and informative design; (3) Lived experiences; and (4) Trust, credibility and connection, suggesting that the design of user‐centred educational resources can drive action, support decision‐making and enhance user trust. These insights informed resource refinements for colour, language clarity, content relevance and navigation options to support their adoption into MS care. Conclusion: This study co‐developed MS‐specific nutrition educational resources to integrate nutrition into MS care. Future research should evaluate their applicability and effectiveness in real‐world settings. Patient or Public Contribution: An MS consumer panel was consulted during the planning phase, and HCPs and plwMS contributed throughout the design process, including feedback on Phase 1 findings and prototypes.